Model‐Driven Multidisciplinary Global Research to Meet Future Needs: The Case for "Improving Radiation Use Efficiency to Increase Yield". Issue 3 (1st May 2019) - Asseng, Senthold; Martre, Pierre; Ewert, Frank; Dreccer, M. Fernanda; Beres, Brian L.; Reynolds, Matthew; Braun, Hans-Joachim; Langridge, Peter; Le Gouis, Jacques; Salse, Jérôme; Baenziger, P. Stephen
Abstract : Improving wheat ( Triticum aestivum L.) yields to meet the projected demand for food in the future requires the talents of diverse scientists. In this article, we present the rationale for crop‐model‐driven, trait‐focused collaborative research emphasizing radiation use efficiency (RUE). Improving RUE is one of the promising avenues to substantially increase potential yields. A collaboration of crop modelers, physiologists, geneticists, plant breeders, and system agronomists is proposed to efficiently create genetic improvements that, when taken to the field, will have regional and global yield impacts. The effort will require a large, internationally integrated science project and related infrastructure such as was recently developed in the Wheat Initiative. The Wheat Initiative is an international consortium of scientists and public and industry funders to sustainably improve global wheat production. The proposed integrated research is applicable to explore other traits and trait combinations and could become a model for yield improvements for major food crops.